The effectiveness of a program based on office activities in simplifying some Arabic grammar rules for early childhood children - Al-Anazi, Muna Abdullah (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed at detecting the effectiveness of a program based on library activities in simplifying some Arabic language rules in the early childhood stage, and revealing the possibility of continuing the effect of a program based on office activities in simplifying some Arabic language rules in the early childhood stage, one month after the program has been implemented. The study sample consisted of (60) children of early childhood children in Hafr Al-Batin, aged 7 to 8 years. The research relied on the semi-experimental approach. The researcher relied on program based on library activities prepared by the researcher and Arabic grammar test., prepared by the researcher. The Research revealed that there are statistically significant differences between the average scores of the children of the experimental and control groups in the post-measurement of some Arabic language rules and their total score in favor of the children of the experimental group, There are statistically significant differences between the average scores of the children of the experimental group in the pre- and post-measurements of some Arabic language rules and their total score in favor of the post-measurement, and there are no statistically significant differences between the average scores of the children of the experimental group in the post and follow-up measurements of some Arabic grammar rules and their total score.
Keywords: A Program Based on Library Activities; Some Arabic Language Rules; Children in Early Childhood